Talent Management dalam Perspektif Organizational Change and Development - Fathul Himam (Faculty of Psychology Universitas Gadjah Mada, 2013)
Entering the global world, within which the communication boundaries among organizations are crossing geographical boundaries, crossing different cultures, and crossing different time zones, the realities of organization as always changing and developing are becoming unavoidable phenomena. Organizations willneed valid and effective strategies to survive within theses changing environments. Human capitals with their high talents are served as major determinant factor for the organizations in reaching their fullcapabilities of successes. This paper tries to offer a contextual perspective in understanding talent management as a strategic organizational intervention. It is directed to understand how human capitals should be managed strategically in order to gains their values as assets in dealing with emerging challenges of boundaryless organizations. It means that talent management does not always lead to individual development model, but it is translated into organizational efforts, i.e. organizational interventions, toincrease its capabilities in dealing with multi-facets-dynamic environmental changing and development. Within this perspective, talent management functions as a driver as well as a parameter for organizations in developing their strategies in facing the ever-changing boundaryless environments. It is a strategic effort todeal with dynamic interactions among organizations within boundaryless situations